THE DROUGHT VARIABILITY ANALYSIS FOR RICE PRODUCTION USING STANDARDIZED PRECIPITATION INDEX (SPI) - Widya Lestari, Ulfa
Indramayu regency is the second largest producer of rice in West Java that is susceptible to drought events. The influence of ENSO give a bad impact on rice production which causes tens of thousands hectares of rice crops suffer parched during drought. The drought variability contributes in the production of rice. One of the anticipation ways for the drought is a SPI-drought index implementation. This drought have to be formulated in several physically controlling factors of drought so that we can estimate the number of early rice production in Indramayu. The utilization of SPI calculation by simply input rainfall data will be estimated the area prone to drought, the frequency of occurrence, and the critical value of rainfall to prevail the drought. As a result, the 12-month SPI value very influenced by ENSO in the Nino 3.4. Furthermore, these results used to study the relation of external factors, which control the ENSO events, such as the value of sunspots through a cloud mechanism and center of the universe mass through a mechanism of the tidal annual formation for the drought events. This study showed that during El Nino event in Indramayu certainly cause drought and lead to a decrease in rice production, meanwhile during the La Nina event may not necessarily affect the rice production, because non-meteorological factors like land area, flood, pest, plant disease, etc . In addition, external factors such as solar activity and the movement of center of mass of the universe also contribute to influence to the formation of a drought by modulating the ENSO event.